"A ground of more than necessary love": Magic and loss in the poetry of K.D. Katrak. Issue 1 (4th March 2017) - Mazzarella, William
Abstract: Known primarily for his flamboyant and turbulent career in advertising, Kersy Katrak was also a remarkable poet. This article makes a case not only for retrieving Katrak's poetic voice, and situating it in relation to his poetic peers in the 1960s and 1970s, but also for exploring the deep relation between Katrak's publicity work and his poetic concerns. The article argues that the link may be drawn through Katrak's lifelong engagement with esoteric practice.